2014
DOI: 10.5899/2014/jgmi-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction VEGF-A expression induced by saffron aqua extract with low frequency electromagnetic field in MCF-7 cell line

Abstract: Background: Studies both invivo and invitro indicated anticancer and antitumor properties of saffron and its component against different human cancer cells which is wildly used as a drug to promote health and fight diseases from ancient time. Angiogenesis, formation of new blood vessels, is regulated by the balances of many stimulating and inhibiting factors. While physiological angiogenesis is under strike control, disruption of this control causes proliferation of a network of blood vessels penetrating into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…There are several active compounds in Saffron such as carotenoids which not only acts as reducing agents for QDs synthesis but also perform as the anti-tumor agent [30]. Inhibition effects of saffron crocin and crocetin constituents have been confirmed on breast cancer cell proliferation in several studies [31][32][33]. It has been reported that saffron extract with all ingredients have synergic effect and are more effective on malignant cells compared to its constituents alone [34].…”
Section: Introductionmentioning
confidence: 99%
“…There are several active compounds in Saffron such as carotenoids which not only acts as reducing agents for QDs synthesis but also perform as the anti-tumor agent [30]. Inhibition effects of saffron crocin and crocetin constituents have been confirmed on breast cancer cell proliferation in several studies [31][32][33]. It has been reported that saffron extract with all ingredients have synergic effect and are more effective on malignant cells compared to its constituents alone [34].…”
Section: Introductionmentioning
confidence: 99%